Vaginal natural orifice transvaginal endoscopic surgery (vNOTES) for benign ovarian cysts is safe and feasible in same-day discharge: a retrospective cohort study - Lulu Wang; Huisheng Ge; Liling Xiong; Aijie Xie; Xian Wu; Juan Huang; Tianjiao Liu; Xin Li; Yujian Jia; Jianmei Liao; Hui Wang; Yonghong Lin; et al. (BMC, 2024)
Abstract Background Advances in minimally invasive surgery and the development of Enhanced Recovery After Surgery (ERAS) have favored the spread of day-surgery programs. Even though Vaginal natural orifice transvaginal endoscopic surgery (vNOTES) is accepted as an innovative treatment for benign ovarian cysts that is rapidly gaining recognition worldwide, the safety and feasibility of same-day surgery (SDS) have yet to be established. Objective This study aimed to evaluate the safety and feasibility of day surgery compared to inpatient surgery of patients undergoing vNOTES for benign ovarian cysts by determining perioperative outcomes. Materials and methods The study consisted of 213 patients who underwent vNOTES for ovarian cystectomy at a single institution from January 2020 to November 2022. Based on the hospital stay, patients were classified into the same-day surgery group (SDSG) and the inpatient surgery group (ISG); after data processing and screening considering the balance of the two groups, SDSG has 83 samples(n = 83), and ISG has 113 samples(n = 113). The patient's demographic characteristics and follow-up data were collected during the perioperative period by doctors and nurses for medical tracking and analysis purposes and 1-month postoperatively by doctors in charge of their operation. Independent sample t-tests were performed to verify if there was any major difference between these two groups for continuous data like age, BMI, and cyst diameter, and Pearson's chi-squared tests were used to test whether there was a major difference between these two groups for categorical data like cyst count, abdominal surgery history and whether their cyst is bilateral ovarian cysts or not. The association between exhaust time and postoperative characteristics and the association between levels of pain and postoperative characteristics were further analyzed to unveil the confounding factors contributing to the same-day discharge method's quick recovery nature. Results Upon performing propensity score matching, 196 patients were finally enrolled in this study for the matched comparison, including 83(42.3%) patients in the SDSG and 113(57.7%) patients in the ISG. There was no statistical difference between the two groups in terms of duration of operation (85.0 ± 41.5 min vs. 80.5 ± 33.5 min), estimated blood loss (27.7 ± 28.0 ml vs. 36.3 ± 33.2 ml), preoperative hemoglobin levels (128.8 ± 13.2 g/L vs. 128.6 ± 14.0 g/L), postoperative hemoglobin difference at 24 h (16.5 ± 15.4 g/L vs. 19.3 ± 9.1 g/L), pelvic adhesions (42 (50.6%) vs. 47 (41.6%)), and postoperative complications (7(8.4%) vs. 4(3.5%)). The SDSG group showed less time of feeding/off-bed/exhaust/urination after surgery, shorter hospitalization duration, a lower postoperative 6-hour pain score, and a lower incidence of analgesic drug use. Multiple linear regression analysis showed that advancing the time of postoperative off-bed activity and feeding reduced the postoperative exhaust time by 0.34 (95% CI: 0.185-0.496, 0.34 h, p < 0.001) and 0.299(95% CI: 0.158-0.443, 0.229 h, p = 0.036) hours. In addition, Ordinal logistic regression revealed a correlation between pain scores and bilaterality of cyst, increasing about 25.98 times the risk of pain levels when ovarian cysts are bilateral (OR: 26.98, 95% CI: 1.071-679.859, P = 0.045). Conclusion In this pilot study, same-day discharge after vaginal natural orifice transvaginal endoscopic ovarian cystectomy is safe and feasible. The vNOTES for ovarian cystectomy combined with the same-day discharge shorten the exhaust time and duration of hospitalization, reduce postoperative pain, and lower the use incidence of analgesic drugs.